Internal Ribosome Entry Site (IRES)-Mediated Translation and Its Potential for Novel mRNA-Based Therapy Development - Rita Marques; Rafaela Lacerda; Luísa Romão (Biomedicines, 2022)
Many conditions can benefit from RNA-based therapies, namely, those targeting internal ribosome entry sites (IRESs) and their regulatory proteins, the IRES trans-acting factors (ITAFs). IRES-mediated translation is an alternative mechanism of translation initiation, known for maintaining protein synthesis when canonical translation is impaired. During a stress response, it contributes to cell reprogramming and adaptation to the new environment. The relationship between IRESs and ITAFs with tumorigenesis and resistance to therapy has been studied in recent years, proposing new therapeutic targets and treatments. In addition, IRES-dependent translation initiation dysregulation is also related to neurological and cardiovascular diseases, muscular atrophies, or other syndromes. The participation of these structures in the development of such pathologies has been studied, yet to a far lesser extent than in cancer. Strategies involving the disruption of IRES–ITAF interactions or the modification of ITAF expression levels may be used with great impact in the development of new therapeutics. In this review, we aim to comprehend the current data on groups of human pathologies associated with IRES and/or ITAF dysregulation and their application in the designing of new therapeutic approaches using them as targets or tools. Thus, we wish to summarise the evidence in the field hoping to open new promising lines of investigation toward personalised treatments.